ØªØ·ÙˆÙŠØ± Ø§Ù„Ù…ÙˆØ§Ø¯ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ù„Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ø§Ù„Ù…ØªÙƒØ§Ù…Ù„Ø© Ø¨Ø¨Ø·Ø§Ù‚Ø§Øª Ø§Ù„ÙƒÙ„Ù…Ø§Øª ÙˆØ§Ù„ØµÙˆØ± ÙÙŠ Ø¶ÙˆØ¡ Ø§Ù„Ù…Ø¯Ø®Ù„ Ø§Ù„Ø³ÙŠØ§Ù‚ÙŠ (Ø¨Ø§Ù„ØªØ·Ø¨ÙŠÙ‚ Ø¹Ù„Ù‰ Ø·Ù„Ø¨Ø© Ù‚Ø³Ù… Ø¥Ø¹Ø¯Ø§Ø¯ Ù…Ø¹Ù„Ù…ÙŠ Ø§Ù„Ù…Ø¯Ø§Ø±Ø³ Ø§Ù„Ø§Ø¨ØªØ¯Ø§Ø¦ÙŠØ© Ø¨Ø¬Ø§Ù…Ø¹Ø© Ù‡Ø§Ø´Ù… Ø£Ø´Ø¹Ø±ÙŠ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬) - Abdul Qodir (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2021)
The alumni of the Study Program of PGMI (Islamic Elementary School Teachers) of Hasyim Asy’ari University, Jombang will become class room teachers in Islamic Elementary Schools. Arabic materials can be usesd as an accomplishment of their teaching duties. This research is conducted to overcome problems faced by them in the teaching of Arabic, particularly many of them didn’t choose Arabic language to teach because they didn’t understand and master Arabic materials. Development of this Arabic textbook is to solve their problems. This research aims at: 1) Developing a textbook for speaking skill through contextual approach integrated with word cards and pictures, 2) Measuring the expediency of the textbook developed for speaking skill through contextual approach integrated with word cards and pictures, and 3) Measuring the effectiveness of the textbook for the students of the study program of PGMI (Islamic Elementary School Teachers) of Hasyim Asy’ari University, Jombang. This research uses research and development method which put before by Dick and Carey. It’s steps are : 1) identification of learning’s objectives, 2) learning analysis, 3) analysis of students and context, 4) determining learning’s objectives, 5) developing assessment instruments, 6) developing learning strategies, 7) developing dan choosing learning materials, 8) designing and doing formative evaluation, 9) revision, and 10) designing and doing summative evaluation. Then, the ten steps adapted according to Belawati which consist of five steps: Analysis, Design, Development, Evaluation and Revision. The data collected are then analyzed qualitatively and quantitatively. The results of the research are: 1) Learning with the textbook uses word cards and pictures. The textbook’s materials consist of words and pictures, a) Kalimah, writed and composed according with Arabic grammar and the topics needed, b) pictures, showed according with words writed. 2) the expediency of the arabic textbook for speaking skill through contextual approach integrated with word cards and pictures with score 90 indicates that the textbook is very good and suitable. 3) the textbook is highly effective to increase the speaking skill of the students of the Study Program of PGMI (Islamic Elementary School Teachers) of Hasyim Asy’ari University, Jombang, which is shown by an increasing average scores from 77,07 at the pre-test and 88,53 at the post-test. This finding proves that this textbook with word cards and pictures can increase the students’ scores up to approximately 11,47 points. Keywords: textbook, speaking skill, contextual approach, word cards and pictures